Empirical analysis: knowledge management, the human focus and intellectual capital for innovation in smart/future universities - Alyami, Nuha; Ahmetoglu, Sehnaz; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
Knowledge management (KM) has been viewed as one of the most important developments in the fields of information studies and management in the modern times. By obtaining, organizing, documenting and sharing knowledge, KM helps complex organizations make better decisions and solve their problems efficiently and effectively. As the highest centres of learning, universities should build information infrastructure and create an atmosphere where academic and non-academic staff, students, researchers, patrons and other stakeholders can take part in various KM sharing actions. The role of knowledge workers in this regard is quite important. By promoting knowledge discovery and use, knowledge workers can bring about changes in the university’s organizational cultures and individual behaviors relative to knowledge. Universities can play an important role in the building and unrestricted development of a knowledge-based society by recruiting and developing skilled and competent knowledge workers and empowering them to manage and leveraging the knowledge assets strategically. In this paper we look for the level of understanding of KM within the universities in Saudi Arabia and the current KM practice undergoing, and how they try to improve and identify the barriers preventing them becoming smart/future universities. As the study showed that many agreed on the importance of KM in their establishments, they either do not apply it, or is not supported by higher positions.